2015
DOI: 10.1021/acs.jmedchem.5b00896
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting the DNA Interaction and Anticancer Activity of Pt(II) N-Heterocyclic Carbene Complexes by Steric Shielding of the Trans Leaving Group

Abstract: Five platinum(II) complexes bearing a (1,3-dibenzyl)imidazol-2-ylidene ligand but different leaving groups trans to it were examined for cytotoxicity, DNA and cell cycle interference, vascular disrupting properties, and nephrotoxicity. The cytotoxicity of complexes 3a-c increased with the steric shielding of their leaving chloride ligand, and complex 3c, featuring two triphenylphosphanes, was the most efficacious, with submicromolar IC50 concentrations. Complexes 3a-c interacted with DNA in electrophoretic mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 45 publications
3
62
0
Order By: Relevance
“…The extent to which our observations may explain anti-angiogenic and vascular disturbing properties of recently reported platinum–metal complexes should be explored. 48,49 Indeed our findings may be relevant to the biological function at the molecular level of the Ru-based NAMI-A, the prototypical anti-metastatic coordination compound, which has undergone clinical trials based on its anti-metastatic properties. 50 …”
Section: Discussionmentioning
confidence: 79%
“…The extent to which our observations may explain anti-angiogenic and vascular disturbing properties of recently reported platinum–metal complexes should be explored. 48,49 Indeed our findings may be relevant to the biological function at the molecular level of the Ru-based NAMI-A, the prototypical anti-metastatic coordination compound, which has undergone clinical trials based on its anti-metastatic properties. 50 …”
Section: Discussionmentioning
confidence: 79%
“…stock solution in H2O for cisplatin. 18 We also found that addition of glutathione (GSH) greatly accelerate the kinetic of reduction of Pt(IV) 19 (see ESI for experimental details). 16 No significant change was observed at concentrations used for in vitro studies.…”
Section: Investigations Of Cytotoxic Activitymentioning
confidence: 89%
“…Moreover, in vivo experiments confirmed that 7 is more effective than oxaliplatin in reducing tumor growth. 53 In fact, an almost two-fold higher tumor volume inhibition (80%) with respect to oxaliplatin was reached in a xenograft mouse models bearing HCT-116 tumor, upon treatment with 10 mg/kg of 7 once every 48 h. Notably, no side effects were observed with compound 7 whereas the treatment of oxaliplatin induced hemorrhagic events.…”
Section: Direct Coordinationmentioning
confidence: 91%
“…53,54 In vitro screening of a series of 1,3-dibenzylimidazolylidene Pt(II) complexes with different leaving groups trans to it (8a-c, Figure 5) showed that the antiproliferative activity strongly depends on the nature and position of this ligand (PPh3, 2-picoline, Cl and NHC, respectively). 53 Interestingly, it was demonstrated that the higher the number of PPh3, which might sterically restrict the contact with DNA or the hydrolysis of the leaving chloride, ligands, the lower the ability and rate to irreversibly bind to double-stranded CT DNA. Finally, the authors suggested that the trend of cell growth inhibition in this series was a result of the ability of the compounds to cause DNA aggregation.…”
Section: Direct Coordinationmentioning
confidence: 99%